The Diffusion of Chlorinated Hydrocarbons in Particles of Activated Carbon - Daniel Bobok; Eva Besedová (Adsorption Science & Technology)
Computed values of the effective diffusion coefficient, D e , ranging from 4.93 × 10 −10 to 5.96 × 10 −10 m 2 /s were obtained from kinetic data for the adsorption of 1,2-dichloropropane from a mixture with air on to activated carbon particles at concentrations within the range 14.94–31.51 g/m 3 . Such kinetic adsorption data were obtained over the temperature range 24.1–25.8°C. Using the dependence D e = f(C A0 ), it was possible to compare the calculated values of D e for 1,2-dichloropropane with the experimental data for 1,2-dichloroethane obtained from adsorption measurements. The values of the effective diffusion coefficients for 1,2-dichloropropane as calculated from its desorption by pure air were within the range 1.67 × 10 −10 –2.01 × 10 −10 m 2 /s at temperatures of 24.0–24.2°C. The considerable difference between the values of the effective diffusion coefficient for 1,2-dichloropropane in activated carbon particles as estimated from adsorption and desorption data may be associated with the non-linear course of the adsorption isotherm.